STRATEGIC COMMUNICATION - OPPORTUNITY AND NECESSITY IN THE CONTEXT OF EXPANSION AND DIVERSIFICATION OF HYBRIDITY - ȚUȚUIANU, Bogdan (Strategic Impact, 2022)
In an era of internet, highly developed technology, and hugely exploited and omnipresent information environment, communication in the field of defence and security has acquired remarkable significance. In an age of expansion and diversification of the hybrid phenomenon, of an assertive geopolitical competition based in large measure on any methods and means employed so as to ensure the fulfilment of own state interests, it is easy to notice the use of media and social networks more than any time before, in order to influence and even manipulate public opinion meant to change perceptions, mislead, polarize and divide. This gave rise to the necessity of emergence of strategic communication concept, developed in the western world, including at the level of North Atlantic Alliance in order to support the achievement of security goals of the Alliance and the Member States. The present article is a plea for raising awareness upon the increased importance of strategic communication, at military and political levels, in the context of expansion and diversification of hybrid phenomenon as a reality that needs revealing and countering, when coming from our opponents, and used for reaching own goals.